2016
DOI: 10.3171/2015.7.peds15101
|View full text |Cite
|
Sign up to set email alerts
|

Utility of diffusion tensor imaging studies linked to neuronavigation and other modalities in repeat hemispherotomy for intractable epilepsy

Abstract: OBJECT Hemispherectomy for unilateral, medically refractory epilepsy is associated with excellent long-term seizure control. However, for patients with recurrent seizures following disconnection, workup and investigation can be challenging, and surgical options may be limited. Few studies have examined the role of repeat hemispherotomy in these patients. The authors hypothesized that residual fiber connections between the hemispheres could be the underlying cause of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Previous studies have shown that patients in whom hemispherectomy has failed are likely to have remaining hemispheric connections, particularly anteriorly, and can benefit from reoperation to complete the disconnection. 11 This new technique may raise concerns that complete disconnection may be inadequately evaluated with the endoscopic view compared to the direct visualization provided by classic open procedures; therefore, we have high standards of close inspection and verification of every disconnection step. We also carefully reviewed the intraoperative endoscopic video of every surgery and verified disconnec-tions radiographically with postoperative tractography in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients in whom hemispherectomy has failed are likely to have remaining hemispheric connections, particularly anteriorly, and can benefit from reoperation to complete the disconnection. 11 This new technique may raise concerns that complete disconnection may be inadequately evaluated with the endoscopic view compared to the direct visualization provided by classic open procedures; therefore, we have high standards of close inspection and verification of every disconnection step. We also carefully reviewed the intraoperative endoscopic video of every surgery and verified disconnec-tions radiographically with postoperative tractography in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…2,5,13 Thus, redo disconnective surgery becomes a good option and is often able to achieve satisfactory outcomes. 2,8 The exact point where disconnection is usually incomplete depends on the technique adopted for hemispheric disconnection and the personal experience of the surgeon. Once this point is identified, more attention must be taken in the initial surgery for this specific step and in the postoperative MRI when looking for reasons of seizure persistence.…”
Section: Incomplete Disconnectionmentioning
confidence: 99%
“…Tractography is particularly helpful for this assessment. 8 From an anatomical point of view, the two hemispheres are connected by commissural fibers basically present in the corpus callosum, the anterior commissure, and the hippocampal commissure. The corpus callosum can be divided into anterior genu (connecting the frontal lobes), rostrum, body (connecting the posterior portions of the frontal lobes and the parietal lobes), and splenium (temporal and occipital connections).…”
Section: Incomplete Disconnectionmentioning
confidence: 99%
“…These detrimental effects are at least partly due to impairing previously unaffected regions of the brain (“kindling”), requiring a speedy decision‐making process . In these children with severe early epileptic encephalopathies of structural origins, both functional and diffusion MRI may play an important role in neurosurgical decision‐making, particularly for initial or repeat hemispherotomy …”
Section: Decision‐makingmentioning
confidence: 99%